(2x-1)*(4x^2+2x+1)-4x*(2x^2-3)=23

Question

(2x-1)*(4x^2+2x+1)-4x*(2x^2-3)=23

in progress 0
Ben Gia 1 year 2020-10-14T04:22:26+00:00 2 Answers 98 views 0

Answers ( )

    0
    2020-10-14T04:23:52+00:00

    Đáp án:

     $x=2$

    Giải thích các bước giải:

     $(2x-1).(4x^2+2x+1)-4x.(2x^2-3)=0$

    $⇔8x^3-1-8x^3+12x=23$

    $⇔12x-1=23$

    $⇔12x=24$

    $⇔x=2$

    0
    2020-10-14T04:24:05+00:00

    Đáp án:

    $x=2$

    Giải thích các bước giải:

    $(2x-1).(4x^2+2x+1)-4x.(2x^2-3)=23$

    $⇔8x^3+4x^2+2x-4x^2-2x-1-8x^3+12x=23$

    $⇔12x=24$

    $⇔x=2$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )